Mediating Role of Entrepreneurship Capability in Sustainable Performance and Women Entrepreneurship: An Evidence from a Developing Country - Poli, Tahmina Akter (Journal of Ecohumanism, 2024)
The research paper determines the influential factors, such as family support and motivation, for entrepreneurship capability (EC) in Small and Medium Enterprise’s sectors in Bangladesh. The study also identifies the medicating role of EC in sustainable performance in SME’s through financial support and motivation factors. The research methodology was focused on quantitative method using reliable instruments for sampling and measurement purposes. This research was conducted on a sample of a total of 250 questionnaires given to SME entrepreneurs using a convenience sampling technique in Bangladesh, and 210 were successfully collected from respondents in the study area. The distribution of questionnaires was conducted through a combination of social media platforms, face-to-face interactions, and Google Forms, where the response rate was 84%. Analysis was conducted through SPSS in Partial Least Squares (PLS) in Structural Equitation Model (SEM). The findings indicate that four out of the five hypotheses were supported, while only one (MT-EC) was rejected. The findings of this research indicate that there is a positive and significant connection between FS, MT, and EC variables. The capabilities of women in entrepreneurship have a notable and positive impact on SP. Moreover, FS and MT have an impact on women's EC and SP. This study determines the research gaps by studying how familial support increases feelings of high self-efficacy and how it affects future behavior of individuals. This study's approach considers environmental and social aspects simultaneously, adding to the prevailing understanding on it.